ANALISA KINERJA REKSA DANA SAHAM BERBENTUK KIK BERDASARKAN RISK ADJUSTED PERFORMANCE METHOD PERIODE 1 JANUARI 2007 – 31 DESEMBER 2009 - Angky Agani Purwanto; Arnold Japutra (Universitas Bunda Mulia, 2017)
The background of this research is the growth of Indonesian people’s interest to put their money for investment in mutual fund. The purpose of this research is to evaluate the performance of the mutual fund which revolves in Indonesia with the risk adjusted return performance method. The subject of this research is the equity mutual fund in Indonesia which have been distributed and being actively sold since 1 January 2007 until 31 December 2009. The object of this research is the return of each mutual fund. The result of this research is Panin Dana Maksima, Pratama Saham, Schroder Dana Prestasi Plus, and Si Dana Saham has the best performance according the risk adjusted return performance method. Key Words- Sharpe ratio, Treynor ratio, and Jensen’s Alpha.